Female Leaders’ Leadership 4.0 Skills in the Context of Industry 4.0 - Šilingienė, Violeta; Stukaitė, Dalia; Bervingienė, Jolanta (Information & Media, 2023)
The article presents the study of Leadership 4.0 skills of female leaders in organizations in context of Industry 4.0. Industry 4.0 and the emergence of new technologies have brought new challenges to organizations. Digital transformation is shaping the need to acquire new skills and competencies to aid in this transition. Presently, possibilities exist to form new insights about the gender leadership, there is a need to identify which Leadership 4.0 skills are important for women in the context of Industry 4.0. The aim of the paper is to reveal the female leaders’ Leadership 4.0 skills in organizations in context of Industry 4.0 transformation. In doing this, qualitative data were collected from Lithuanian business organizations using semi-structured interviews with thirteen female managers. The research reveals six groups of Leadership 4.0 skills: visionality, change management, creativity, continuous learning, interpersonal skills, and personal characteristics. Research disclosed that collaboration, educating others, dealing with resistance to change, building relationships, curiosity, communicating change, risk taking, perception of complexity and development is important for female leaders for Leadership 4.0. This study enhances theoretical foundation of the relationship between Leadership 4.0 skills and female leadership, providing empirical evidence on the topic.